Highly efficient electric drive with vision system for traction applications in heavy tracked vehicles - I. Yu. Kholodilin; A. V. Korzhov; M. A. Grigoriev; Yu. I. Khokhlov; N. V. Savosteenko (Омский научный вестник)
A new type of electric motor as a traction drive DET400 based on a field regulated reluctance machine (FRRM) provides high energy efficiency and high specific torque. A comparison is made between FRRM and various types of traction electric drives. The issues of designing the FRRM are considered, the geometric parameters of the electric machine are optimized to achieve the maximum specific indicators. To expand the functionality and ensure operational safety, it is proposed to introduce computer vision into the electronic control system. As a result, the FRRM is designed for traction applications based on the real requirements of a Russian-made crawler tractor.